Guru sebagai Influencer: Membangun Generasi Cerdas dan Berkarakter di Era Digital - Apriani Putri Fajtriansyah; Fadillah Julya Putri; Herlini Puspika Sari (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This study examines the role of teachers as influencers in 21st-century education, particularly in developing students’ intelligence and character through the use of digital media and technology. The digital transformation requires teachers to serve not only as transmitters of knowledge but also as public figures capable of providing positive influence through digital behavior and communication. The purpose of this study is to analyze how teachers perform their roles as educational influencers and how this impacts students’ intellectual and character development. This research employs a literature study method by reviewing scientific sources such as books, articles, journals, and relevant research reports. The analysis was conducted using a descriptive-analytical approach to identify patterns, ideas, and strategies used by teachers in integrating character values and digital literacy. The findings indicate that teachers with strong digital competence and personal integrity are able to create positive influence through educational content, digital role modeling, and ethical communication. The implications highlight the importance of strengthening teachers’ digital literacy, educational policy support, and continuous professional training to create a digital learning ecosystem that is character-based, adaptive, and responsive to contemporary challenges.